Educação Inclusiva: desafios e possibilidades na prática docente - Ramos, Sarah Pinto (Brasil, 2019)
Education is a right guaranteed in the Constitution of the Federative Republic of Brazil of 1988 as a fundamental right, and the need to educate for heterogeneity is indispensable. In this sense, the objective of this paper was to analyze the challenges and possibilities of inclusive education experienced by teachers of the public schools of regular education in the municipality of Humaitá-AM, considering the school structure, initial, continuing education and methodologies focused on an education that prioritizes the heterogeneity. The research was conducted in nine public schools of regular education and the federal institute of Amazonas, with fifteen teachers, five of science, six of biology and four of chemistry. The methodology that guided the research was descriptive field qualitative, involving the application of a questionnaire to teachers. The results showed that the biggest challenges of inclusive education in the municipality is the lack of preparation of public school teachers, lack of continuing education, inappropriate physical structures, among other challenges; Possibilities highlight the need for more partnerships between schools and other institutions, for undergraduate courses and curricula to be adapted for better training of future teachers and more investments. In general, we consider the need to believe, invest time and resources so that inclusive education is no longer just a formality, an aspect guaranteed in legislation, but a reality in regular schools and Brazilian universities.